Data-driven comparison of urban sustainability towards sustainable urban development under sustainable development goals (SDGs): a review based on bibliometric analysis - Wang, Di; Dong, Liang; Di, Siyan (Frontiers in Energy Research, 2023)
As urbanization has been deepened rapidly, the issue of sustainability has become increasingly prominent, and urban sustainability should be the key to the sustainable agenda raised by UN. This study combines bibliometrics and text mining to analyze the research progress of urban sustainability. A total of 1031 keywords from 240 documents screened by the PRISMA method are coded to draw heat maps in accordance with the sustainable triple bottom line principle and its cross-scope (Environment, Society, Economics, Environment & Society, Environment & Economics, Society & Economics, Environment, Society & Economics) with its emphasis on 17 SDGs. The results indicate that the existing relevant research has still focused on the research on environmental protection. Besides the general “sustainability” topics, “land use”, “decision-making”, “green city”, “eco-city” have been more discussed than others. For the SDGs, the SDG6, 7, 9, 11, 12, 15 represent clean water, affordable and clean energy, industry, innovation and infrastructure, sustainable cities and communities, responsible consumption and production and life on land, respectively. Only a small part of the research has begun to focus on the sustainable development of the community. More comprehensive and complete insights should be gained into sustainable development.